POSTURAL CONTROL IN ATHLETES: A COMPARISON OF INJURY RISK BASED ON TRAINING METHODS (The Research of Medical Science Review, 2025)
This study examines the impact of various training methods on performance metrics, injury risks, and their interrelationships among athletes. A total of 100 participants, divided equally across four training groups (Strength Training, Balance/Stability Training, Plyometric Training, and Sport-Specific Drills), were assessed for injury risk levels (low, moderate, high) and performance outcomes, including Y-Balance Score, Force Plate Stability, Single-Leg Stance Duration, and FMS Score. Statistical analyses, including One-Way ANOVA, Chi-Square tests, and correlation analysis, were conducted to evaluate differences, associations, and interrelationships among the variables. The One-Way ANOVA revealed significant differences between training groups (p = 0.02), indicating that training types influence performance and injury outcomes. The Chi- Square analysis (p = 0.026) demonstrated a significant association between training methods and injury risks, with Plyometric Training participants exhibiting higher injury risks, whereas Strength and Balance/Stability Training groups were linked to lower risks. Correlation analysis showed a strong positive relationship between Y-Balance Score and FMS Score (r = 0.65), highlighting the connection between balance and functional movement. Conversely, Force Plate Stability demonstrated negative correlations with performance measures, suggesting a potential trade-off between static stability and dynamic performance. The findings align with previous studies emphasizing the efficacy of Strength and Balance/Stability Training in reducing injury risks and enhancing functional outcomes, while highlighting the injury risks associated with Plyometric Training. This study underscores the need for tailored, sport-specific training programs to optimize performance and minimize injury risks, contributing to the growing body of evidence in athletic training and injury prevention.